PEMBUATAN PRODUK CAMILAN SEHAT BERBAHAN KEARIFAN LOKAL (KETELA POHON DAN TEPUNG LELE) UNTUK MENINGKATKAN GIZI BALITA - kiswati, Kiswati; Jamhariyah, Jamhariyah; Sugijati, Sugijati (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2024)
Semenggu Village produces a lot of cassava (cassava) as a food source of carbohydrates. However, limited processing capacity, taste and less than optimal implementation of marketing strategies are one of the problems in the village. For this reason, it is necessary to empower the community in Bintoro Village, especially Semenggu Village, in processing cassava so that it can be used as a food product of high economic value. Methods for implementing community service in Semenggu Village, Bintoro Subdistrict include : 1)Training and direct practice to make, process and produce various cassava products, 2) Teaches simple management through organizational structures and teaches simple bookkeeping, 3) Provision of facilities and infrastructure as well 4) Assistance in the form of consultation and guidance in producing processed cassava. The training was attended by 20 mothers in the Semenggu Village area, Bintoro Subdistrict, The mothers were given counseling about several cassava snack products and their development. One of them is by making mini samilers with a mixture of catfish, serving them wrapped in plastic and adding various flavors to the snack product (corn flavor, barbeque flavor, balado flavor, cheese flavor, original and others). The mini samiler product is made from a mixture of African catfish meat, apart from providing a savory taste, it also has high nutritional value. The delicious taste after adding various flavors to the samiler will give the impression of classy food even though it is made from cassava and catfish flour. In terms of taste, the catfish gives a very tasty snack taste. After being given to children and parents, they really liked it and all of them gave positive evaluations compared to just plain fried.